Pengaruh Model Flipped Clasroom dengan Media Interaktif Adobe Flash Terhadap komunikasi Matematis Siswa dan Pemecahan Masalah Matematis Siswa SMK Pasudan 1 Kota Serang - Dayurni, Popi; Hutabarat, Tika Elisabet Aprilia; Nurlaela, Siti Sarah; Wida, Fa'izatul; Hanipah, Hanipah; Audi, Nadia Putri (Jurnal Inovasi dan Teknologi Pendidikan, 2025)
This study discusses the effect of the flipped classroom learning model supported by the Adobe Flash application on the mathematical communication skills and mathematical problem solving of students at SMK Pasundan 1 Kota Serang. This study uses a quantitative approach with an experimental method with the Pre-Experimental type. The study was conducted in one class only (experimental class Using a one group pretest posttest design. In this study, an initial test was carried out before being given treatment (pretest) then treatment was carried out (flipped classroom learning model with the help of the Adobe Flash application), then a final test was given after being given treatment (posttest). The results showed that there was a significant difference between the learning outcomes of students in the pretest and posttest classes. Students who were given treatment with the flipped classroom learning model using Adobe Flash showed an increase in mathematical communication skills and mathematical problem solving that were better than students who were given treatment with conventional learning models. These results indicate that the Flipped Classroom Model with Adobe Flash Interactive Media can improve the mathematical communication skills and mathematical problem solving of students at SMK Pasundan 1 Kota Serang